Expressões não manuais: o teatro como estratégia no ensino e aprendizagem da Língua Brasileira de Sinais - LIMA, José Willen Brasil (2019)
The present study is a discussion of the teaching / learning of Brazilian Sign Language - Libras. The research started from the notes that most of the courses in which I was present, there is a greater concern in the seizure and acquisition of signals having no attention to the other parameters in this case the non-manual expressions. As a result, the objective of this study was to investigate the relevance of non-manual expressions in the teaching learning process of pounds, with the tool the use of theater as an increase of methodology in language teaching. It is a descriptive study and a qualitative approach performed with a group of six participants working in a theater group in the city of Nova Esperança do Piriá (PA). The data collection instrument was a questionnaire with eight open and closed questions, outlined from the scope of this study. The results show that the learner a new language, in this case Pounds, have immense difficulty when exposed to random signals, given that this language uses non-Manais aspects to schedule a grammatical sentence or the intonation of a sentence. The use of this feature in the theater gave more freedom to the participants to create phrases or interpret requested texts